2005
DOI: 10.1577/a05-008.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Short‐Term Exposure to High Temperature as a Tool to Suppress the Reproductive Development of Channel Catfish for Aquaculture

Abstract: Short-term exposures to elevated temperatures reduce germ cell numbers in the gonads of some fishes, suggesting that heat treatment may be a viable method for delaying or suppressing reproductive development in cultured fishes. The objective of this study was to determine the effects of high temperatures on early gonadal development in channel catfish Ictalurus punctatus. Twenty-three-day-old (after hatching) channel catfish were exposed to temperatures of 27ЊC (control), 34ЊC, and 36ЊC for 4 weeks. Groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Heat induction of sterility has been reported for some species of fish and other vertebrates (Byerly et al, 2005;Lue et al, 1999a;Strüssmann et al, 1998), but the underlying cellular and molecular mechanisms of heat-induced germ cell loss are not clearly understood. Temperature, an environmental factor, is able to modulate gene expression by epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat induction of sterility has been reported for some species of fish and other vertebrates (Byerly et al, 2005;Lue et al, 1999a;Strüssmann et al, 1998), but the underlying cellular and molecular mechanisms of heat-induced germ cell loss are not clearly understood. Temperature, an environmental factor, is able to modulate gene expression by epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In chicken, heat treatment causes a significant reduction in egg production, egg weight, ovarian weight, and the number of large follicles (Rozenboim et al, 2007). Most scrotal male mammals lose germ cells due to heat stress (Socher et al, 1997), while heat treatment impairs follicular development in female cattle (Wolfenson et al, 1995) and induces germ cell death in some species of fish (Byerly et al, 2005;Ito et al, 2003;Majhi et al, 2009a;Strüssmann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This form of germ cell death is associated with various pathological conditions such as cryptorchidism, varicocele, and hydrocele (VanDemark and Free 1970;Harrison 1975;Kandeel and Swerdloff 1988). Heat-induced gonadal degeneration and germ cell loss have been recently reported also in fishes such as pejerrey (Odontesthes bonariensis; Ito et al 2003a), channel catfish (Ictalurus punctatus; Byerly et al 2005), and Florida largemouth bass (Micropterus salmoides floridanus; C. A. Strüssmann and R. Patiño, unpublished observations) and might be widespread in this taxon (reviewed in Strüssmann andPatiño 1995, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the control of this process would facilitate the production of sterile fish, a desirable technology to improve the growth of farmed fish (Hunter and Donaldson 1983;Dunham 1990;Byerly et al 2005) and reduce the ecological impact of exotic species should they escape from captivity. In this context, we designed this experiment to obtain basic information on the cell/tissue dynamics and characteristics of warm water-induced gonadal degeneration and germ cell loss in subadult pejerrey of both sexes and to probe by histochemical and biochemical methods the occurrence of apoptosis during these processes.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also showed, for the first time, that high temperature alone can be effective as a sterilization agent in a sexually mature freshwater fish. This was previously shown only for fish incubated at high temperatures from the larval phase or as juveniles [24][25][26][27].…”
Section: Discussionmentioning
confidence: 80%